Principles of planar near-field antenna measurements - Gregson, Stuart Fraser; McCormick, John (Lead radar systems engineer); Parini, Clive (London, United Kingdom Institution of Engineering and Technology, 2007)
The book covers the following areas: planar near-field antenna measurements; Maxwell equation; and electromagnetic wave propagation.
Electronic reproduction.
Keywords: Antennas (Electronics); Electronic books